Mudanças climáticas e risco ao patrimônio cultural em Ouro Preto – MG - Brasil - Silvia Helena Zanirato; Wagner Costa Ribeiro (Confins)
The loss of cultural heritage buildings would entail significant prejudice for the memory and history of the country, as well as damage to thousands of people whose jobs depend from Ouro Preto's condition as patrimonial city. The focus of this article is to address the exposure to risk of the built heritage in Ouro Preto, which can increase with the scenarios of global climate change, in particular the worsening conditions of occurrence of landslides. The text is therefore organized into four parts, besides the introduction. Initially we discuss the concern of UNESCO, management agency of cultural heritage at international scale, as to the effects of climate change on world heritage, as well as the identified scenarios for Brazil and for the Southeast in particular. The second part presents the extent to which the morphology of the city and how its occupation occurred made it prone to landslides that put at risk both population and cultural heritage. Then, we present points where it is possible to perceive threats to heritage buildings, followed by concluding remarks.